Analisis Gaya Bahasa Kiasan Pada Lirik Lagu "o, Tuan" Karya .Feast - Nofrisha Arkana Raid; Lalita Melasarianti; Nur Indah Sholikhati (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
This study aims to describe the use of figurative language in the lyrics of the song “O, Tuan” from the album *Membangun & Menghancurkan* by .Feast through a stylistic analysis. This study employs a descriptive qualitative approach using the Simak Bebas Libat Cakap (SBLC) method and note-taking techniques to identify, classify, and analyze the forms of figurative language that appear in the song lyrics. The results of the study indicate that there are six types of figurative language, based on Gorys Keraf’s classification, found in the lyrics of “O, Tuan,” namely metaphor, personification, antonomasia, synecdoche, hypallage, and innuendo. These six figures of speech play a role in building the expressive power of the lyrics, such as metaphors and personification, which provide poetic and emotional nuances, as well as antonomasia and synecdoche, which offer variations in the representation of meaning. Additionally, hypallage and innuendo provide a more complex interpretive layer through deviations from standard structure and the subtle or implied conveyance of meaning. This finding confirms that .Feast employs language choices in an aesthetic, symbolic, and deliberate manner to reinforce the artistic message and social critique intended to be conveyed. Thus, the figurative language in the lyrics of “o, Tuan” is not merely an aesthetic element but also functions as a linguistic strategy that enriches meaning, deepens the message, and reinforces the social critique and existential reflection on humanity’s limitations regarding time and death conveyed symbolically and poetically to the listener. Keywords: Stylistics, Figurative Language, Feast